Relationships between glacier and rock glacier in the Maritime Alps, Schiantala valley, Italy - RIBOLINI, ADRIANO; PAPPALARDO, MARTA; CHELLI A; GUGLIELMIN M (Quaternary Research, 2007)
In the Schiantala Valley of the Maritime Alps, the relationship between a till-like body and a contiguous rock glacier has been analyzed using geomorphologic, geoelectric and ice-petrographic methodologies. DC resistivity tomographies undertaken in the till and in the rock glacier show the presence of buried massive ice and ice-rich sediments, respectively. Ice samples from a massive ice outcrop show spherical gas inclusions and equidimensional ice crystals that are randomly orientated, confirming the typical petrographic characteristics of sedimentary ice. The rock glacier formation began after a phase of glacier expansion about 2550±50 14C yr BP. Further ice advance during the Little Ice Age (LIA) overrode the rock glacier root and caused partial shrinkage of the pre-existing permafrost. Finally, during the 19th and 20th centuries, the glacial surface became totally debris covered. Geomorphological and geophysical methods combined with analyses of ice structure and fabric can effectively interpret the genesis of landforms in an environment where glaciers and permafrost interact. Ice petrography proved especially useful for differentiating ice of past glaciers versus ice formed under permafrost conditions. These two mechanisms of ice formation are common in the Maritime Alps where many sites of modern rock glaciers were formerly occupied by LIA glaciers.